STRATEGI PEMASARAN DALAM RANGKA PENINGKATAN PENJUALAN PRODUK ROKOK LUCKY STRIKE MILD PT. BENTOEL INVESTAMA, TBK WILAYAH PEMASARAN DEPOK - Teguh Prakoso (JURNAL LENTERA AKUNTANSI, 2019)
This research was written by Tri Setyo Waluyo, August to September 2016, with the title "Marketing Strategies In Order To Increase Sales Products Lucky Strike Cigarettes Mild PT. Bentoel Investama Tbk Territory Marketing Depok ". This study aims to obtain a better overview of the results of a SWOT analysis of the marketing strategy in an effort to increase sales. And generates information or rupiah a percentage increase that can be achieved from olehan marketing strategies in order to improve penjualanultan.Methods using descriptive qualitative approach because researchers wanted to know how far the company steps in implementing marketing strategies and be able to compete with its competitors in order to increase its market share. The research proves that the SWOT Analysis PT. Bentoel Investama Tbk can be identified that can be factors Strength (strength), Weakness (weakness), Opportunities (opportunities) and Threats (threats) as follows; (1) The power of such products, prices and promotions due to extremely has the power to conduct the competition in the market; (2) the weakness is in the distribution channel because there are still many shortcomings that must be corrected; (3) Opportunities include macro external environment; (4) The threat of such an external environment Micro. The company's position is based on the analysis of total factor Internal and External companies using IE matrix models aiming to acquire the right strategy to be applied in a company. Based on these factors, to have obtained a score of IFAS and EFAS = 2.522 = 2.507 so it appears that cigarette company's business Growth through horizontal integration. In this position, the company can carry out the expansion of the market, develop products, increase product quality, or increasing access to a wider market, and improve the production facilities to increase the number of sales.Key words: marketing strategies, increase sales, SWOT analysis